The Investment Effect on Prosperity in Indonesia with Economic Development as an Intervening Variable - Suharti, Sri; Prasetyo, Yoyok; Naufal, Muhammad Dzaki; Aminullah, Ali (Universitas Islam Indonesia, 2022)
Indonesia is rich with natural resources, which attract investors. However, it has not impacted an insufficient level of prosperity, as shown by a low level of education and income per capita. The study aims to determine the effect of investment as measured by Global Competitive Index (GCI) as the independent variable, Human Development Index (HDI) as the dependent variable on prosperity, and Gross Domestic Product (GDP) as an intervening variable to measure economic development. The research used a descriptive quantitative framework, supported by data from books, journals, and other online sources. The data were analyzed with a linear regression statistical model using SPSS.25. The results indicate that investment has no significant direct effect on prosperity, yet, it has a significant indirect effect on prosperity through economic development. The current imbalance in economic and education progress illustrates that today's development is against Islamic principles, e.g., divinity, justice, and sustainability. These principles are the keys to solving the problem of prosperity in Indonesia. Thus, to increase prosperity, the government needs to increase public access to economic development by improving education and health facilities, especially in rural areas, and the independence of the people to manage the country's wealth.